Molecular epidemiology and resistance modulation of Streptococcus spp. in subclinical goat mastitis in Pakistan - Ashraf Ali; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Hamza Rasheed; Maria Batool; Kehkshan Shahid; Gulbaz Anwar; Mahpara Safdar (Small Ruminant Research, 2026)

Molecular insights, resistance profiling, and in silico structural modeling of extended-spectrum beta-lactamase-producing E. coli in camels - Mahpara Safdar; Muhammad Ijaz; Arslan Ahmed; Muhammad Umar Javed; Kehkshan Shahid; Maria Batool; Gulbaz Anwar; Hamza Rasheed; Ashraf Ali (Veterinary Research Communications, 2026)

Molecular biology of the novel anticancer medications: a focus on kinases inhibitors, biologics and CAR T-cell therapy - Elia-Luna Abdo; Imad Ajib; Jason El Mounzer; Mohammad Husseini; Gharam Kalaoun; Tatiana-Maria Matta; Reine Mosleh; Fidel Nasr; Nour Richani; Alia Khalil; Anwar Shayya; Hady Ghanem; et al. (Inflammation Research, 2025)

Correction to: Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Evaluation of the perception of climate change and its implications across various geo-physical regions of Kashmir Himalayas - Hilal Ahmad Parrey; Mohammad Shafi Bhat; Shamim Ahmad Shah; Mir Sumira; Irshad Ahmad Thoker; Muhammad Mubashar Dogar; Sanju Purohit; Muhammad Ahmad Dogar; Maria Anwar (Natural Hazards, 2025)

Exploring the Role of Plant Growth-Promoting Bacteria in Biodegradation of Plastic: A Review - Haris Maqbool; Fazal Ur Rehman; Izhar Khan; Nadeem Ullah; Muhammad Anwar Sajad; Nazir Mohammad; Maria Kalsoom; Shafiq Ur Rehman; Muhammad Farooq Hussain Munis; Malka Saba; Hassan Javed Chaudhary (Water, Air, & Soil Pollution, 2025)

The efficacy of egg albumin nanoparticles adjuvanted Clostridium perfringens type D toxoid vaccine in rabbits - Mehwish Saeed; Saad Zafar; Zarreen Sajjad; Rizwan Aslam; Sultan Ali; Muhammad Shahid Mahmood; Mueed Aayan; Maria Sophy; Saqib Umer; Sajjad Ur Rahman; Muhammad Naveed Anwar (Brazilian Journal of Microbiology, 2025)

Phytochemical screening and antimicrobial potential of Chenopodium quinoa extract against pathogenic bacterial strains - Hina Anwar; Arslan Habib; Muhammad Usman Taj; Muhammad Azhar Ali; Ayesha Munir; Marva Shafi; Maria Saddique; Sohaib Ahmed; Henrique D. M. Coutinho (Vegetos, 2024)

Moderately deep tillage enhances rapeseed yield by improving frost resistance of seedling during overwintering - Chunyun Wang; Zongkai Wang; Ali Mahmoud El-Badri; Maria Batool; Sumera Anwar; Xianling Wang; Mingqiang Bai; Yunhao You; Bo Wang; Jing Wang; Zhenghua Xu; Jie Kuai; et al. (Field Crops Research, 2023)

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Molecular Detection, Phylogenetic Analysis, and Genetic Diversity of Theileria annulata, Babesia bigemina, and Anaplasma marginale in Cattle in Three Districts of Egypt - Khaled Mohamed El-Dakhly; Waleed M. Arafa; Saad Soliman; Omima Ramadan Abdel-Fatah; Ahmed Anwar Wahba; Maria D. Esteve-Gasent; Patricia J. Holman (Acta Parasitologica, 2020)

Tumor-associated proteases and inhibitors in gastric cancer: analysis of prognostic impact and individual risk protease patterns - Heike Allgayer; Rudolf Babic; Klaus Uwe Grützner; Bianca C. M. Beyer; Anwar Tarabichi; Friedrich Wilhelm Schildberg; Markus Maria Heiss (Clinical & Experimental Metastasis, 1998)